Role of TaALMT1 malate‐GABA transporter in alkaline pH tolerance of wheat. (20th August 2020) - Kamran, Muhammad; Ramesh, Sunita A.; Gilliham, Matthew; Tyerman, Stephen D.; Bose, Jayakumar
Abstract: Malate exudation through wheat ( Triticum aestivum L) aluminium‐activated malate transporter 1 (TaALMT1) confers Al 3+ tolerance at low pH, but is also activated by alkaline pH, and is regulated by and facilitates significant transport of gamma‐aminobutyric acid (GABA, a zwitterionic buffer). Therefore, TaALMT1 may facilitate acidification of an alkaline rhizosphere by promoting exudation of both malate and GABA. Here, the performance of wheat near isogenic lines ET8 (Al +3 ‐tolerant, high TaALMT1 expression) and ES8 (Al +3 ‐sensitive, low TaALMT1 expression) are compared. Root growth (at 5 weeks) was higher for ET8 than ES8 at pH 9. ET8 roots exuded more malate and GABA at high pH and acidified the rhizosphere more rapidly. GABA and malate exudation was enhanced at high pH by the addition of aluminate in both ET8 and transgenic barley expressing TaALMT1 . Xenopus laevis oocytes expressing TaALMT1 acidified an alkaline media more rapidly than controls corresponding to higher GABA efflux. TaALMT1 expression did not change under alkaline conditions but key genes involved in GABA turnover changed in accordance with a high rate of GABA synthesis. We propose that TaALMT1 plays a role in alkaline tolerance by exuding malate and GABA, possibly coupled to proton efflux. Abstract : Aluminium‐activated malate transporter 1 in wheat roots is activated by high pH and enhanced by aluminate to release gamma‐aminobutyric acid and malate, which facilitates rhizosphere acidification and tolerance to high pH.